Sustainable Management of Water Resources Reusing Municipal Wastewater in the Toll Land Approach - Saeid Ghafoori (Water and Wastewater Consulting Engineers Research Development, 2021)
Reuse of treated wastewater is becoming a common source of extra renewable water source in regions and countries with water-scarcity. The expansion of the urban population and the increase in the sewage networks will increase the amount of municipal wastewater. The produced wastewater can become a source of renewable water that can be used for various non-potable reuse, specifically. In the current research study, the newly established Pardis city has been selected as a case study for using recycled water (reuse of treated wastewater) for sustainable water resources management. To accomplish the overall objective of the study, Geo-land method for water reuse is employed. For this study the use of regional wastewater facility instead of centralized wastewater treatment facility as well as the related capital cost savings, job opportunities, and environmental benefits were evaluated. Statistical analyses were performed based on multiple factors and classification indicators. The results showed that the highest amount of savings and financial surplus income, 36.17% and 31.25%, respectively, of the overall savings and income as the main priority and recommendation in place of water source will occur in the study area. On the other hand, savings and financial surplus for the group that does not need to use treated wastewater is only for 1.15% of the total study area which stands as the last priority.Results obtained from this study revealed that prioritization of decentralized use of wastewater for urban areas was a highly efficient plan for a significant part of residential areas, while reducing water consumption along with economic savings and increasing regional income happened. The proposed study can also be used as a sustainable water resources management decision-making tool for Pardis city officials.